Redefining Language Learning Through AR/VR Technologies: Immersive Environments for Enhancing Cultural Understanding and Linguistic Proficiency - Ishak Bagea; Mariama Bah; Ryan Teo (International Journal of Language and Ubiquitous Learning, 2026)
Background. Augmented Reality (AR) and Virtual Reality (VR) technologies have the potential to revolutionize language learning by providing immersive, interactive environments that enhance cultural understanding and linguistic proficiency. Traditional language learning methods often fail to fully engage learners in real-life contexts, limiting their exposure to authentic language use and cultural nuances. AR and VR offer a unique opportunity to simulate real-world scenarios, enabling learners to experience language and culture in ways that were previously unimaginable. Purpose. This study aims to explore the integration of AR and VR technologies into language learning platforms to enhance both linguistic proficiency and cultural understanding. The research focuses on evaluating how immersive environments can improve learners’ ability to engage with language in practical, context-driven settings. Method. The study uses a mixed-methods design, incorporating both qualitative and quantitative data. Participants were exposed to AR and VR-based language learning modules, and their linguistic performance, cultural understanding, and engagement were assessed through pre- and post-tests, surveys, and interviews. Observational data from classroom settings were also analyzed to evaluate the effectiveness of the immersive learning experience. Results. The findings show that learners who engaged with AR/VR-based language learning demonstrated significant improvements in both linguistic proficiency and cultural understanding. Additionally, participants reported higher levels of motivation and engagement compared to traditional methods. Conclusion. AR and VR technologies offer significant potential in language learning by providing immersive experiences that enhance both linguistic and cultural learning. The study highlights the importance of integrating innovative technologies into educational frameworks to foster more effective and engaging language acquisition.